Differences in the effects and action modes of gut commensals against dextran sulfate sodium-induced intestinal inflammation - Dingwu Qu; Zhennan Gu; Saisai Feng; Leilei Yu; Fengwei Tian; Hao Zhang; Wei Chen; Qixiao Zhai (Food Science and Human Wellness)
Inflammatory bowel disease (IBD) is a complex relapsing inflammatory disease in the gut and is driven by complicated host-gut microbiome interactions. Gut commensals have shown different functions in IBD prevention and treatment. To gain a mechanistic understanding of how different commensals affect intestinal inflammation, we compared the protective effects of 6 probiotics (belonging to the genera Akkermansia, Bifidobacterium, Clostridium, and Enterococcus) on dextran sulfate sodium (DSS)-induced colitis in mice with or without gut microbiota. Anti-inflammatory properties (ratio of interleukin (IL)-10 and IL-12) of these strains were also evaluated in an in vitro mesenteric lymph nodes (MLN) co-culture system. Results showed that 4 probiotics (belonging to the species Bifidobacterium breve, Bifidobacterium bifidum, and Enterococcus faecalis) can alleviate colitis in normal mice. The probiotic strains differed in regulating the intestinal microbiota, cytokines (IL-10, IL-1β and interferon (IFN)-γ), and tight junction function (Zonulin-1 and Occludin). By constrast, Akkermansia muciniphila AH39 and Clostridium butyricum FHuNHHMY49T1 were not protective. Interestingly, B. breve JSNJJNM2 with high anti-inflammatory potential in the MLN model could relieve colitis symptoms in antibiotic cocktail (Abx)-treated mice. Meanwhile, E. faecalis FJSWX25M1 induced low levels of cytokines in vitro and showed no beneficial effects. Therefore, we provided insight into the clinical application of probiotics in IBD treatment.